The Role of ESG Disclosure in Corporate Performance and Investment Decision-Making - Pratiwi, Ayu Putri; Edeh, Friday Ogbu (Yayasan Sinergi Kawula Muda, 2024)
The integration of Environmental, Social, and Governance (ESG) factors into corporate strategies has become increasingly relevant in modern business and investment landscapes. This study examines the impact of ESG disclosure on financial performance, the influence of regulatory frameworks, and the challenges associated with ESG adoption. A systematic review of academic literature reveals that transparent ESG reporting enhances investor confidence, reduces capital costs, and fosters long-term business value. Regulatory interventions, such as the Corporate Sustainability Reporting Directive (CSRD), play a crucial role in improving ESG disclosure quality, yet inconsistencies in reporting standards and data reliability concerns persist. Despite the positive correlation between ESG disclosure and corporate performance, challenges such as skepticism regarding ESG metrics and variations in reporting practices pose obstacles to full integration. This study underscores the necessity of refining ESG audit mechanisms and developing standardized reporting frameworks to ensure credibility and comparability across industries and regions. Future research should focus on exploring sector-specific ESG impacts, refining regulatory measures, and leveraging technological advancements to enhance ESG reporting accuracy. Strengthening ESG integration not only aligns businesses with evolving stakeholder expectations but also contributes to sustainable economic growth and corporate accountability.